2017
DOI: 10.4172/2573-0312.1000132
|View full text |Cite
|
Sign up to set email alerts
|

Yoga and Mental Health: A Review

Abstract: The need for effective population mental health promotion approaches is urgent as mental health concerns are escalating globally and current allopathic treatment regimens are insufficient to bring people towards the state of mental well-being (citation). Successfully alleviating stress has the potential to promote wellbeing and prevent illness. Worldwide, yoga is gaining popularity as an accessible, acceptable and cost-effective practice for mind and body. People are turning to yoga for mental health improveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
1
8
0
1
Order By: Relevance
“…[20][21][22][23][24][25][26] The beneficial effects of yoga on mental health have been comprehensively reported in earlier studies. 27 A recent pilot study has shown the potential of combined yoga and naturopathy treatment for relieving anxiety and depression of COVID-19-affected people. 24 Evidence from previous studies suggests a benefit of consistent practice of yoga and pranayama for relaxation of both mind and body: The practice is argued to activate the parasympathetic nervous system and relieve anxiety and stress.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24][25][26] The beneficial effects of yoga on mental health have been comprehensively reported in earlier studies. 27 A recent pilot study has shown the potential of combined yoga and naturopathy treatment for relieving anxiety and depression of COVID-19-affected people. 24 Evidence from previous studies suggests a benefit of consistent practice of yoga and pranayama for relaxation of both mind and body: The practice is argued to activate the parasympathetic nervous system and relieve anxiety and stress.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have proposed that yoga can provide a complementary therapy in the battle against the novel coronavirus influencing both, the physical as well as the mental wellbeing of people (Bhatia, 2020;Nagendra, 2020;Sahni et al, 2021;Sharma, 2020;Telles, 2020). Potential of yoga for helping in depression has been comprehensively reported earlier (Shroff & Asgarpour, 2017). Effectiveness of yoga in reducing depression, anxiety, and stress in 68 cancer patients undergoing radiotherapy has also been reported in a previous study (Banerjee et al, 2007).…”
Section: Introductionmentioning
confidence: 67%
“…It appears that deep slow breathing in combination with movement and other aspects of yoga haw ability to bring person a greater sense of tranquility. We have base evidence that yoga can reduce symptoms of anxiety and depression [18,19]. However, additional investigation in this field are highly recommended, specifically because of the positive relevant psycho-physiological rationale.…”
Section: Discussionmentioning
confidence: 99%